Brief version of the job satisfaction scale: structural anddistributive evaluation of their scores - Boluarte Carbajal, Alicia (2015)
The job satisfaction evaluation allows us to know and explain several behavioral results of a worker such as his job performance. This study analyzes the internal structure of the brief version by Warr, Cook and Wall’s Job Satisfaction Scale (1979), which is designed to unidimensionaly measure the job satisfaction construct with items related to intrinsic and extrinsic satisfaction. The sample was composed by 88 professionals from a rehabilitation institution located in Metropolitan Lima, who were given the full version of the instrument (16 items), to examine the abbreviated version and derive a new one. We performed a confirmatory factor analysis (CFA) to evaluate the factorial structure through the modeling of structural equations. It was found that a latent dimension is valid for the comprehensive instrument, and a new version was obtained with different items, greater explained variance, and higher factorial loads. The reliability estimates were acceptable. The score distribution was unusually set to a Wakeby model. The results are discussed in the usage context of this new version and the distribution of the scores.